2022
DOI: 10.1108/ebr-07-2021-0148
|View full text |Cite
|
Sign up to set email alerts
|

The effect of talent management and leadership styles on firms’ sustainable performance

Abstract: Purpose This study aims to develop a framework that examines how different leadership styles influence talent management (TM) and how these leadership styles and TM influence firms’ sustainable performance considering the moderating role of environmental dynamism. Design/methodology/approach To achieve these objectives, an empirical survey was conducted among 480 participant firms in Greece. Hierarchical regression was performed to test the hypotheses. Findings This study reveals the significance of author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 78 publications
(108 reference statements)
0
18
0
Order By: Relevance
“…Lack of knowledge and experience of sustainability practices, lack of non-monetary motivation mechanisms and tedious paperwork are major obstacles to successful sustainability. Specific training and development programs could assist employees to improve the skills that would enable them to better exhibit sustainability behaviors (Kafetzopoulos and Gotzamani, 2022). Furthermore, leaders have to create an environment which is conducive to sustainability by encouraging employees to share their ideas, information and risk taking, fostering sustainable development (Iqbal et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of knowledge and experience of sustainability practices, lack of non-monetary motivation mechanisms and tedious paperwork are major obstacles to successful sustainability. Specific training and development programs could assist employees to improve the skills that would enable them to better exhibit sustainability behaviors (Kafetzopoulos and Gotzamani, 2022). Furthermore, leaders have to create an environment which is conducive to sustainability by encouraging employees to share their ideas, information and risk taking, fostering sustainable development (Iqbal et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…They further noted that managers need to pay close attention to their environment when making strategic and operational decisions. Moreover, Kafetzopoulos and Gotzamani (2022) point out that in a highly volatile environment with fleeting opportunities and ever-present threats from competitors, environmental turbulence reduces the competitive position and affects sustainable performance. Moreover, this study tested the mediating role of internal organizational factors between ED and sustainability.…”
Section: Discussionmentioning
confidence: 99%
“…The question of how strategic leaders drive firm performance extends back decades and is one of the most studied areas of management (Bergh et al ., 2016). One of the critical choices of the strategic leader is the leader-talent team, which has also been explored extensively in the literature (Kafetzopoulos and Gotzamani, 2022; Wang et al ., 2014). We need specific research to get a more nuanced picture of the role of leadership and talent in emerging technology environments.…”
Section: Theoretical Foundation and Hypothesesmentioning
confidence: 99%
“…Scholars, such as DeGroot et al (2000), found out that charismatic leadership is a significant and valuable dimension to anchor the beneficial outcomes of an organization such as leader and employee effectiveness and employee job satisfaction and commitment. Charismatic characteristics have a way of influencing individuals and organizational performance (Kafetzopoulos and Gotzamani, 2022; Milosevic and Erin Bass, 2014). Weber (1968) was the first person to use the word “charisma” in his work and define charismatic leader as the individual who could contribute to social change.…”
Section: Literature Reviewmentioning
confidence: 99%